Urban development with dynamic digital twins in Helsinki city - Hämäläinen, Mervi (Wiley Open Access, 2021)
A dynamic digital twin is a feasible solution that can be employed to build real‐time connectivity between virtual and physical objects. Industries like manufacturing, aerospace and healthcare utilise dynamic digital twins for simulation, monitoring and control purposes, but recently, this nascent technology has also attracted the interest of urban designers. Due to the novelty of the dynamic digital twin in urban design, this research study addresses the concept of digital twin technology and investigates its applicability in so‐called smart city settings. Drawing on results from research interviews and examples from the Digital Twin project in Helsinki city, the research illustrates that solid data infrastructure forms the foundation for urban digital twins and the development of future smart city applications and services. Furthermore, data‐enriched digital twins evidently accelerate smart city experimentations and strengthen both learning and knowledge‐based decision‐making. Digital twins have also proved that they offer an environment in which smart city practitioners can bridge multi‐stakeholder urban design teams through one digital platform.
Keywords: Digital twin; smart city; smart city experimentation; stakeholders; fi=Markkinointi|en=Marketing|